Blood pressure from the optical Aktiia Bracelet: a 1-month validation study using an extended ISO81060-2 protocol adapted for a cuffless wrist device. Issue 4 (August 2021) - Vybornova, Anna; Polychronopoulou, Erietta; Wurzner-Ghajarzadeh, Arlène; Fallet, Sibylle; Sola, Josep; Wuerzner, Gregoire
Abstract : Objective: The objective of this study (NCT04027777) was to assess the accuracy and precision of the Aktiia Bracelet, a CE-marked noninvasive optical blood pressure (BP) monitor worn at the wrist, over a period of 1 month. Methods: In this study, participants aged between 21 and 65 years were recruited. The clinical investigation extended the ISO81060-2:2013 standard to the specificities of cuffless devices. Each BP assessment consisted of the simultaneous recording of optical signals with Aktiia Bracelet and double-blinded auscultation by two trained observers in the standard sitting position. The algorithms of Aktiia Bracelet further processed the recorded optical signals to perform a signal quality check and to calculate uncalibrated estimates of systolic BP (SBP) and diastolic BP (DBP). These estimates were transformed into mmHg using a subject-dependent calibration parameter, which was calculated using the first two available reference measurements per subject. Results: Eighty-six participants were included in the analysis. The mean and SD of the differences between Aktiia Bracelet estimates and the reference (ISO81060-2 criterion 1) were 0.46 ± 7.75 mmHg for SBP and 0.39 ± 6.86 mmHg for DBP. The SD of the averaged paired difference per subject (ISO81060-2 criterion 2) were 3.9 mmHg for SBP and 3.6 mmHg for DBP. Conclusion: After initialization and during 1 month, the overall accuracy of Aktiia Bracelet satisfied validation criteria 1 and 2 of ISO81060-2 in the sitting position. The Aktiia Bracelet can be recommended for BP measurement in the adult population.